Use of Intravenous Ketorolac as Postoperative Analgesic in Neonates: A Prospective Study in Chittagong, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Introduction: Painful exposures have the potential for deleterious consequences upon neonates. Although Opioids and NSAIDs play important role in postoperative pain control, those are associated with side effects. We have studied use of ketorolac as postoperative analgesic in Bangladeshi neonates.Methods: This prospective study was undertaken in the Department of Pharmacology & Therapeutics and Department of Pediatric Surgery, Chittagong Medical College, Chittagong, Bangladesh from July 2013 to June 2014. All postoperative neonates received either ketorolac intravenously or acetaminophen per rectally every 8 hrs for 72hrs. Pain was assessed every 8 hours and as-needed basis by CRIES scale.Results: Out of 60 patients, 30 patients were in Ketorolac group and 30 in Acetaminophen group. Pain score was significantly low in Ketorolac group. However, heart rate, respiratory rate and temperature did not change much in either group. Four patients had unusual bleeding tendency in Ketorolac group and bleeding time in this group was significantly low on 1st postoperative day. Serum creatinine showed no significant change in either group. Two patients in each group developed edema. One patient in each group expired due to sepsis.Conclusions: Ketorolac has better analgesic efficacy than acetaminophen as postoperative analgesic in neonates, although associated with bleeding tendency.Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 11-16